A multi-site case study of community-clinical linkages for promoting HPV vaccination. Issue 7 (3rd August 2019) - Brandt, Heather M.; Vanderpool, Robin C.; Curry, Susan J.; Farris, Paige; Daniel-Ulloa, Jason; Seegmiller, Laura; Stradtman, Lindsay R.; Vu, Thuy; Taylor, Victoria; Zubizarreta, Maria
ABSTRACT: Human papillomavirus (HPV) vaccination rates in the U.S. are suboptimal, requiring innovative partnerships between community and clinical entities to remedy this issue. A rigorous evaluation of HPV-related community-clinical linkages (CCLs) was conducted to understand their components, processes, and outcomes to increase HPV vaccination. Cancer Prevention and Control Research Network (CPCRN) investigators explored CCLs in their communities employing an iterative, case study approach. Information describing nine CCLs on HPV vaccination was collected from representatives from the community organization and clinical setting. Thematic content analysis was used to analyze and interpret data. Five CCLs included a federally qualified health center as the clinical partner, and five included a non-profit organization as the community partner. Five reflected clinically focused integration wherein engagement occurs in the community but vaccine delivery and follow-up occur in the clinical setting. The main impetus was the need to improve HPV vaccination and a community's strong interest in preventing cancer. Noted critical components were a designated person to support the CCL and funding. Results will guide HPV vaccination promotion, education, and intervention efforts. CCLs provide an opportunity to study the adaption, integration, and enhancement of evidence-based approaches to increase HPV vaccination.